Structural equation modeling of consumer purchase intention toward synthetic functional foods - Rezai, Golnaz; Phuah, Kit Teng; Mohamed, Zainal Abidin; Shamsudin, Mad Nasir (Routledge, 2014)
Functional foods are gaining greater popularity around the world. They are not just a new category of food products marketed for their health benefits, but their competitive market has made consumers become more favorable toward firms that are involved in this industry. The public is increasingly concerned about health and food-related risks. They tend to make decisions on food consumption, food storage, and food preparation on a more ideal perspective based on health and safety. Therefore, the objective of this study is to determine the factors and intention of Malaysian consumers to purchase synthetic functional foods. Structural equation modeling is used to accomplish the objectives of this study with the feedback received from the 2,004 households who were interviewed through a structural questionnaire. The results show that the most influential factors influencing consumer purchasing intention toward synthetic functional foods are perceived benefits followed by attitude and subjective norms.